Psychometric Properties of the Turkish Version of the Palliative Care Attitude Scale (T-PCAS-9) in Cancer Patients - Demir Çam, Sevgi; İşcan Ayyildiz, Neşe; Evcimen, Hasan; Çil, Timüçin; Bozkurt Duman, Berna (Makara Journal of Health Research, 2025)
Background: A reliable, validated Turkish measurement tool will allow researchers to measure the impact of attitudes towards palliative care on other health outcomes in individuals with chronic and critical illness. This study aimed to examine the Turkish psychometric properties of the Palliative Care Attitude Scale (PCAS-9) for individuals with cancer. Methods: The Turkish adaptation of the PCAS-9 (T-PCAS-9) included 505 cancer patients, who were aged >18 years, had a diagnosis of cancer, and no mental problems. The factor structure of the T-PCAS-9 was examined using exploratory factor analysis, confirmatory factor analysis, convergent-divergent validity, and measurement invariance analysis. Results: The three-factor structure with factor loadings >0.5 was found to have convergent-divergent validity and measurement invariance. The internal consistency coefficients of the T-PCAS-9 were >0.7. Conclusions: The T-PCAS-9 was found to be a valid and reliable measurement tool for assessing palliative care attitudes in the Turkish population.